The specificity of antibody responses in cattle naturally exposed to Fasciola hepatica. - Ortiz-Oblitas, P. (2000)
Fasciola hepatica causes significant morbidity and mortality in dairy cattle in the Andean region of Cajamarca, Peru, where prevalence of infection of up to 78% has been reported. ELISA and Western blot analyses were used to characterise antibody responses in dairy cattle to adult F. hepatica to excretory-secretory (E/S), somatic (SO) and surface (SU) antigens. Three groups of dairy cattle - calves, heifers and adult cows - naturally exposed to F. hepatica in this region, were monitored every 2 months over a 2-year period. Calves, heifers and adult cows all had antibodies which recognised a 28kDa protein in the SO preparation, whereas only adult cows had antibodies that recognised a 28kDa protein in E/S products. All three groups of cattle responded to a 60-66kDa group of proteins in E/S and SU preparations and a 17kDa antigen in SO products was recognised by antibodies from cows and heifers but not calves. The total antibody response to E/S antigens measured by ELISA, increased over time in calves and remained constantly high over the 2-year period in all three groups of cattle. Slight fluctuations in the antibody response occurred in the group of heifers and cows coinciding with seasonal changes in the level of challenge.